COEFFICIENTS EFFECTIVENESS OF THE MEASURES OF PHYSICAL RESTRAINT BY POLICE OFFICERS OF MIA OF UKRAINE - Malolepshuy, S. B.; Kalyuzhnuy, М. G.; Khatsayuk, О. V. (Honor and Law, 2019)
The problem of developing criteria for determining the level of effectiveness of the measures of physical influence and determine the most effective combination of methods to force offenders detained in various conditions of service and police officers of MIA of Ukraine.